Employee consultation and information in multinational corporations - Vandamme, J. (Routledge, 2018)
During a period characterised by both prolonged recession and the increasing complexity of enterprises, informing and consulting with workers becomes all the more important. It is therefore not surprising that the European Commission of the EEC's proposal in favour of a directive concerning such activities attracted attention and created controv
Keywords: International business enterprises -- Europe -- Employees.; Collective bargaining -- International business enterprises -- Europe.; International business enterprises -- Employees -- Legal status, laws, etc. -- Europe.; Négociations collectives -- Entreprises multinationales -- Europe.; BUSINESS & ECONOMICS -- General.; Collective bargaining -- International business enterprises; International business enterprises -- Employees; International business enterprises -- Employees -- Legal status, laws, etc.; Europe